1977
DOI: 10.1139/v77-567
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic routes to 2′,3′-cyclopropanated and 2′,3′-unsaturated nucleosides

Abstract: . Can. J. Chem. 55,3996 (1977). Cyclopropyl glycopyranosides which solvolyze via a stabilized cyclopropyl carbinyl-oxocarbonium ion react under neutral conditions with nucleoside bases in nitromethane at 200°C to give good yields of the corresponding cyclopropanated nucleosides. Under similar conditions hex-2-enopyranosides (which solvolyze by allyl-oxocarbonium ions) do not react. However, under catalysis by mercuric bromide or acetic acid, the corresponding 2',3' unsaturated nucleosides are formed although a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1978
1978
2009
2009

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…This extreme stability was exploited for the preparation of 2'-3'-cyclopropanated nucleosides, e.g. 20 (Scheme 6), [23] by merely subjecting the cyclopropyl glycoside 16 or its homoallyl relative 17 to boiling nitromethane containing the heterocyclic base. Scheme 6.…”
Section: Cyclopropanated Pyranosides: An Ave-nue To Chrysanthemic Acimentioning
confidence: 99%
“…This extreme stability was exploited for the preparation of 2'-3'-cyclopropanated nucleosides, e.g. 20 (Scheme 6), [23] by merely subjecting the cyclopropyl glycoside 16 or its homoallyl relative 17 to boiling nitromethane containing the heterocyclic base. Scheme 6.…”
Section: Cyclopropanated Pyranosides: An Ave-nue To Chrysanthemic Acimentioning
confidence: 99%
“…The study of rearrangement products from d-xylulose (93) with amines and amino acids (Scheme 29) was very important to rationalize the general aspects concerning the tendency of rearrangement of different ketoses [106]. d-Xylulose underwent the rearrangement easily followed by d-fructose and l-sorbose.…”
Section: Range Of Componentsmentioning
confidence: 99%
“…An example of the complexity of the mixture of possible products is the reaction of 2-amino-2-deoxy-d-glucose hydrochloride with ammonia, as conducted by Taha [114] (Scheme 32). He found five main products, which were the unreacted starting material, the cyclization products, 2-methyl-6-d-arabinosylpyrazine (104), 2-methyl-5-d-arabinosyl-3-d-erythrosylpyrazine (105), 2,5-bis-(d-arabinosyl)pyrazine (106), and a dark-brown amorphous substance which consisted of products of further decomposition. From this it can be concluded that careful control of the reaction conditions is very important for the formation of the products.…”
Section: Scheme 31mentioning
confidence: 99%
See 2 more Smart Citations